Synthesis of Bacterial Oligosaccharide Augmented Through Flow Chemistry - Florek, John (Tufts University Tisch Library, 2026)
Thesis (Ph.D.)--Tufts University, 2025.; Submitted to the Dept. of Chemistry.; Advisor: Clay Bennett.; Committee: Rebecca Scheck, and Samuel Thomas.; Keyword: Chemistry